PENGEMBANGAN SISTEM INFORMASI INVENTARIS PADA KANTOR LURAH BERINGIN KOTA JAMBI: Information System, Goods Inventory, Goods Data Collection. - Mulyati , Sri; Oktaviani, Vebby (JURNAL AKADEMIKA, 2021)
Information and communication technology has a great influence on office work, it can be carried out easily and quickly. Office activities are in handling mail, office communication, mail delivery, archive management, and inventory of goods in the office. By using information technology in data processing, it will produce data speed, renewal of facilities to increase speed of information and spread access to parts of the organization. The process of inventorying goods at the Beringin Village Office, Jambi City has used a computer but the processing process is not optimal. So that data errors often occur, data loss, data manipulation, inaccurate data and even difficult to find previous data archives. So the process of monitoring the inventory of these goods is not going well. To overcome this problem the use of computers is very necessary in order to achieve optimal service, so it is hoped that the inventory process of goods can run quickly and smoothly and reduce errors or data manipulation that can occur in data collection of inventory items. The same research and it is hoped that this research can overcome the problems that exist in the Beringin Village Office, Jambi City. Furthermore, the author tries to make a material or equipment information system design for employees so that there are no shortages or disappointments in carrying out their duties.